Challenges of public procurement in Afghanistan: a case study of Finance and administrative directorate in Kunar - Ziauddin (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2020.